Type IIIB and IV hypoplastic thumb reconstruction with non-vascularized fourth metatarsal. (September 2020) - Liu, Bo; Chen, Shanlin; Chow, Esther Ching San; Li, Pengcheng; Liu, Kun; Yang, Chen
We treated 16 patients with 17 hypoplastic thumbs (eight Type IIIB and nine Type IV) using a non-vascularized fourth metatarsal transfer with a rotational flap and multi-staged reconstruction. The average age at the first operation was 24 months. The average follow-up time was 46 months. All patients achieved reasonable hand function and were able to use the reconstructed thumb to grip small and large objects. The operated thumb achieved an average Kapandji score of 6.7 and average pinch strength of 0.9 kg. There were two cases of graft nonunion. All parents are satisfied with the function and appearance of the reconstructed thumb and donor foot. We conclude that non-vascularized fourth metatarsal transfer is a feasible reconstruction method for patients with Types IIIB and IV hypoplastic thumbs. The reconstruction allows for the preservation of a 5-digit hand with reasonable function and appearance and minimal donor site morbidity, although long-term growth of the metatarsals still need to be monitored. Level of evidence: IV